A SYSTEMATIC REVIEW OF DIRECT MEDICAL COSTS AND COMORBIDITIES IN HEART FAILURE - Kana Mukti Nugroho; Trimurti Andayani; Susi Ari Kristina (Pharmacy Department, Math and Sciences Faculty, Udayana Univerity, 2025)
Background: Heart failure (HF) often coexists with multiple comorbidities, which may substantially increase healthcare resource use. However, economic evaluations often overlook the specific cost impact of comorbid conditions in HF patients. Objective: To systematically review and quantify the excess direct medical costs and markup factors associated with comorbidities in patients with heart failure. Methods: A structured literature search was conducted across four databases (PubMed, Embase, ScienceDirect, and Google Scholar) on June 28, 2025. Observational studies reporting direct medical costs of HF patients with and without comorbidities were included. All cost values were standardized to 2024 USD using the Consumer Price Index (CPI) and converted using average exchange rates. The methodological quality of included studies was assessed using criteria adapted from Huber et al. (2015). A total of six studies, all conducted in the United States, met the inclusion criteria. Narrative synthesis was performed due to heterogeneity in cost reporting. Results: Across the six studies, comorbidities significantly increased HF-related costs. Mark-up factors ranged from 0.64 to 2.15, with the highest excess costs observed in patients with hyperkalemia (USD 39,543), drug use disorder (USD 27,783), and cancer (USD 19,379). In contrast, some comorbidities, such as Alzheimer’s disease, ischemic heart disease, and type 2 diabetes mellitus, were associated with lower costs, possibly due to end-of-life care patterns or system-level cost controls. Conclusion: Comorbidities impose a substantial and variable economic burden on HF patients. Findings highlight the need for multi-country studies, standardized cost methodologies, and the inclusion of indirect costs and HF severity stratification in future research. Keywords: Comorbidities; Direct medical costs; Economic burden; Heart failure; Mark-up factor.